Genome-wide association mapping of biochemical traits and its correlation with MYMIV resistance in mungbean (Vigna radiata L. Wilczek) - Manju Kohli; Hina Bansal; Muraleedhar Aski; Gyan P. Mishra; B. R. Shashidhar; Anirban Roy; Soma Gupta; Subodh K. Sinha; Brijesh Kumar Mishra; Nikki Kumari; Atul Kumar; Ranjeet Ranjan Kumar; et al. (Scientific Reports)
Abstract The mungbean yellow mosaic India virus (MYMIV, Begomovirus vignaradiataindiaense) causes Yellow Mosaic Disease (YMD) in mungbean (Vigna radiata L.). The biochemical assays including total phenol content (TPC), total flavonoid content (TFC), ascorbic acid (AA), DPPH (2,2-diphenyl-1-picrylhydrazyl), and FRAP (Ferric Reducing Antioxidant Power) were used to study the mungbean plants defense response to MYMIV infection. A wide range was recorded for the Area Under Disease Progress Curve (AUDPC; 1.75-1266.98) and coefficient of infection (CI; 0.33–45.53). In YMD susceptible genotypes, significant variations were observed for TPC [2001.27-2834.13 mgGAE/100 g dry weight (DW)], TFC (252.65–341.30 mg/100 g DW), AA (40.33–64.69 mg/100 g DW), DPPH (32.11–53.47% scavenging effect DW), and FRAP (48.99-101.22 µmol Fe2+/g DW). Similarly, in resistant genotypes also wide range was recorded for TPC (1788.50-2286.38 mgGAE/100 g DW), TFC (206.12–337.32 mg/100 gDAS samples varied from 384. 6.46–47.64% scavenging effect DW), and FRAP (53.68-114.24 µmol Fe2+/g DW). Except for FRAP, other studied parameters were in the lower range in the resistant genotypes than the susceptible genotypes. Genome-wide association studies (GWAS) of 132 genotypes have identified 31,953 single nucleotide polymorphism (SNPs). MLM (Mixed Linear Model) and BLINK (Bayesian-information and Linkage-disequilibrium Iteratively Nested Keyway) models have identified 119 shared SNPs for various biochemical traits and MYMIV resistance. The key candidate genes include VRADI09G06940 (YMD resistance, TIR-NBS-LRR class, chr. 9), VRADI01G05030 [flavonoid biosynthesis; MYB65 transcription factor (TF); chr. 1], VRADI03G07600 (phenol biosynthesis; GATA TF 16; chr. 3), VRADI04G08470 (ascorbic acid; heat shock protein 70 kDa protein; chr. 4), VRADI04G07510 (FRAP; subtilisin-like protease SBT1.9; chr. 4), and VRADI05G02870 (DPPH; vacuolar protein sorting-associated protein 2; chr. 5). The identified genomic resources will enhance mungbean genomics and facilitate the advancement of genomic-assisted breeding in mungbean.